PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN PT. BEDJOE OETOMO KULON PROGO - Tri Wahyuni, Endang; fitri setyaningsih; Imam Basri, Anidita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This research was conducted to examine the effect of organizational culture, work motivation, and organizational commitment to organizational citizenship behavior (OCB) of PT. Bedjoe Oetomo Kulon Progo. The type of this study is quantitative research that employs 65 respondents. Data collection techniques were carried out by interviews and questionnaires. The results of this study indicate that organizational culture partially has a positive and significant impact on organizational citizentional behavior (OCB) with a regression coefficient of 0,404 and significance value of 0,006. Work motivation partially has a positive and significant impact on organizational citizenship behavior (OCB) with a regression coefficient of 0,363 and significance value of 0,009. Organizational commitment partially has a positive and significant impact on organizational citizenship behavior (OCB) with a regression coefficient of 0,518 and significance value of 0,013. Organizational culture, work motivation, and organizational commitment simultaneously have a significant impact on organizational citizenship behavior (OCB) with a significance value of 0,000. Therefore, all the hypotheses in this research are accepted.